Frequency Of Raised Mean Platelet Volume In Patients With Acute Coronary Syndrome In HIT Hospital Taxila - Faiza Batool; Kausar Malik; Lubna Meraj; Khalid Mehmood Tariq; Tooba Iqbal; Neelum Zaka (Journal of Rawalpindi Medical College)
To determine the frequency of raised Mean Platelet Volume (MPV) in patients with acute coronary syndrome (ACS) in HIT Hospital Taxila.